Long-lasting responses with chemotherapy followed by T-cell therapy in recurrent or metastatic EBV-related nasopharyngeal carcinoma - Secondino, Simona; Pedrazzoli, Paolo; Basso, Sabrina; Bossi, Paolo; Bianco, Alba; Imarisio, Ilaria; Pagani, Anna; De Cicco, Marica; Muscianisi, Stella; Casanova, Michela; Morosi, Carlo; Bergamini, Cristiana; et al. (Frontiers in Immunology, 2023)
Background: Refractory or metastatic nasopharyngeal carcinoma (NPC) patients have a poor prognosis due to the lack of effective salvage treatments and prolonged survival by means of combination chemotherapy being described only for a minority of younger patients with oligometastatic disease. Targeting the Epstein -Barr virus (EBV) proteins expressed in NPC cells has been shown to be a feasible strategy that could help control systemic disease. Methods: Between 2011 and 2014, 16 patients with recurrent/metastatic EBV-NPC received first-line chemotherapy (CT) followed by 2 doses of autologous cytotoxic EBV specific Tlymphocytes (15-25 x 10 7 total cells/dose, 2 weeks apart), based on our previous studies showing the feasibility and efficacy of this infusion regimen. Cumulative overall survival (OS) and median OS were analysed in the whole population and according to specific clinical and biological parameters.Results: All patients received the planned T-cell therapy schedule, 9 after reaching partial (n=5) or complete (n=4) disease remission with CT, and 7 after failing to obtain benefit from chemotherapy.No severe adverse events were recorded. Patients who received cytotoxic T-lymphocytes (CTLs) had a cumulative 10-year OS of 44%, with a median OS of 60 months (95% CI 42-62). Patients responding to CT, with oligometastatic disease (<3 disease sites), and plasma EBV-DNA <1000 copies/mL had a better outcome.Autologous EBV-specific CTLs transplanted following conventional first-line CT demonstrated promising efficacy with several patients obtaining long-lasting disease control. The rationale provided by this study, with the crucial role likely played by the timing of CTL administration when trying to induce synergy with conventional treatment needs to be confirmed in a prospective controlled trial.